2022
DOI: 10.1177/1329878x221094374
|View full text |Cite|
|
Sign up to set email alerts
|

Visibility and invisibility in the aged care sector: visual representation in Australian news from 2018–2021

Abstract: The skyrocketing number and severity of issues in Australian aged care led to the establishment of the Royal Commission into Aged Care Quality and Safety in 2018. Yet, compared to other Royal Commissions, media coverage has been relatively muted, and public awareness and engagement with aged care issues has been uneven. Journalists bear a significant responsibility for shaping the national conversation about aged care, and ensuring this demographic is reflected in the news Australians consume. Due to their uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These issues were persistent before the COVID-19 pandemic, with scholars documenting how media imagery during that event has further ostracized this cohort. As analyzed within the Australian context, visual communication researchers Thomson et al ( 2022 ) found news media coverage to be isolating and marginalizing, generic and vague. Their qualitative representation analysis of aged care captured how those in these settings were represented “with a distant, often de-contextualized or trivialized, and non-representative understanding” (p. 16), such as through visual tropes such as aged and wrinkled hands.…”
Section: Introductionmentioning
confidence: 99%
“…These issues were persistent before the COVID-19 pandemic, with scholars documenting how media imagery during that event has further ostracized this cohort. As analyzed within the Australian context, visual communication researchers Thomson et al ( 2022 ) found news media coverage to be isolating and marginalizing, generic and vague. Their qualitative representation analysis of aged care captured how those in these settings were represented “with a distant, often de-contextualized or trivialized, and non-representative understanding” (p. 16), such as through visual tropes such as aged and wrinkled hands.…”
Section: Introductionmentioning
confidence: 99%
“…As the Royal Commission observed, neglect in aged care has continued unabated, with relatively little community engagement or awareness accorded to this important social problem. Media coverage of abuse and neglect in aged care has often focused on depersonalized and anonymized accounts, leading to an absence of individual stories, faces, and voices of older people featured in the stories purportedly reporting on their experiences ( Thomson et al, 2022 ).…”
mentioning
confidence: 99%